2012
DOI: 10.2208/jscejer.68.iii_1
|View full text |Cite
|
Sign up to set email alerts
|

Formation and Role of Bacterial Community in the Sediment Bed of Open Channel Receiving Johkasou Effluent: Multivariate Statistical Analysis Interpretation

Abstract: To obtain information that can be used as reference for improving the environment inside and surrounding the open channels receiving johkasou effluent, the formation and correlation of sediment bed bacterial density with water quality were evaluated with multivariate statistical analysis based on measured data for water and sediment samples collected for 8 times from 6 sites of an open channel that receives johkasou effluent in a residential area of Gifu Prefecture, Japan. Statistical analysis included princip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
5

Relationship

5
0

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 30 publications
0
12
0
1
Order By: Relevance
“…The interactions between the viruses in the water and the viruses in the sediment, intended as attachment of the viruses onto the sediment particles and their re-suspension from the sediment bed into the water phase, possibly occurred due to the strong correlation between F-RNA bacteriophages in the water and Qβ in the sediment and to the significantly positive correlation of F-RNA bacteriophages in the water with the VS and DS. As suggested by Rehmann and Soupir (2005), the re-suspension of microbes from the sediment bed can be a major source for the stream water 8,36) . Previous studies have also shown that the water flow over the sediment can affect the vertical diffusive flux of solutes because the solute concentration profile near the sediment/water interface varies with the flow velocity 8,37) .…”
Section: Iii_676mentioning
confidence: 92%
See 4 more Smart Citations
“…The interactions between the viruses in the water and the viruses in the sediment, intended as attachment of the viruses onto the sediment particles and their re-suspension from the sediment bed into the water phase, possibly occurred due to the strong correlation between F-RNA bacteriophages in the water and Qβ in the sediment and to the significantly positive correlation of F-RNA bacteriophages in the water with the VS and DS. As suggested by Rehmann and Soupir (2005), the re-suspension of microbes from the sediment bed can be a major source for the stream water 8,36) . Previous studies have also shown that the water flow over the sediment can affect the vertical diffusive flux of solutes because the solute concentration profile near the sediment/water interface varies with the flow velocity 8,37) .…”
Section: Iii_676mentioning
confidence: 92%
“…Correlation analysis was performed using the non-parametric Spearman's rank correlation as not to assume normality of any parameters 24) . The terms "strong", "moderate", and "weak" were applied to factor loading and absolute loading values >0.75, 0.75-0.50, and 0.50-0.30, respectively 8) . All tests were carried out at 5% significant level.…”
Section: (4) Statistical Analysismentioning
confidence: 99%
See 3 more Smart Citations